Particle Focusing in Staged Inertial Microfluidic Devices for Flow Cytometry - Oakey, John (2010)
Microfluidic inertial focusing has been demonstrated to be an effective method for passively positioning microparticles and cells without the assistance of sheath fluid. Because inertial focusing produces well-defined lateral equilibrium particle positions in addition to highly regulated interparticle spacing, its value in flow cytometry has been suggested. Particle focusing occurs in straight channels and can be manipulated through cross sectional channel geometry by the introduction of curvature. Here, we present a staged channel design consisting of both curved and straight sections that combine to order particles into a single streamline with longitudinal spacing. We have evaluated the performance of these staged inertial focusing channels using standard flow cytometry methods that make use of calibration microspheres. Our analysis has determined the measurement precision and resolution, as a function of flow velocity and particle concentration that is provided by these channels. These devices were found to operate with increasing effectiveness at higher flow rates and particle concentrations, within the examined ranges, which is ideal for high throughput analysis. Further, the prototype flow cytometer equipped with an inertial focusing microchannel matched the resolution provided by a commercial hydrodynamic focusing flow cytometer. Most notably, our analysis indicates that the inertial focusing channels virtually eliminated particle coincidence at the analysis point. These properties suggest a potentially significant role for inertial focusing in the development of inexpensive flow cytometry-based diagnostics and in applications requiring the analysis of high particle concentrations.